Bacterial diversity and real‐time PCR based assessment of linA and linB gene distribution at hexachlorocyclohexane contaminated sites. (3rd September 2013) - Lal, Devi; Jindal, Swati; Kumari, Hansi; Jit, Simran; Nigam, Aeshna; Sharma, Pooja; Kumari, Kirti; Lal, Rup
<x xml:space="preserve">Abstract</x> The disposal of hexachlorocyclohexane (HCH) muck has created large number of HCH dumpsites all over the world from where the harmful HCH isomers are leaking into the environment. Bacteria have evolved at such contaminated sites that have the ability to degrade HCH. Degradation of various HCH isomers in bacterial strains is mediated primarily by two genes: linA and linB which encode dehydrochlorinase and haloalkane dehalogenase respectively. In this study we explored one such highly contaminated HCH dumpsite located in Lucknow, Uttar Pradesh, India. To assess the biostimulation potential of the contaminated site, microbial diversity study and real‐time PCR based quantification of lin genes was carried out. The soil samples from dumpsite and surrounding areas were found to be highly contaminated with HCH residue levels as high as 1.8 × 105 mg kg−1. The residues were detected in areas upto 13 km from the dumpsite. Sphingomonads, Chromohalobacter, and Marinobacter were the dominant genera present at the dump‐site. Role of Sphingomonads in HCH degradation has been well documented. The highest copy numbers of linA and linB genes as determined using real‐time PCR were 6.2 × 104 and 5.3 × 105, respectively, were found in sample from the dump site. The presence of Sphingomonads, linA, and linB genes from HCH contaminated soil indicates the presence of indigenous bacterial communities capable of HCH degradation.